CpG oligodeoxynucleotide nanomedicines for the prophylaxis or treatment of cancers, infectious diseases, and allergies - Hanagata N (Dove Medical Press, 2017)
Nobutaka Hanagata1,2 1Nanotechnology Innovation Station, National Institute for Materials Science, Tsukuba, Ibaraki, 2Graduate School of Life Science, Hokkaido University, Sapporo, Hokkaido, Japan Abstract: Unmethylated cytosine-guanine dinucleotide-containing oligodeoxynucleotides (CpG ODNs), which are synthetic agonists of Toll-like receptor 9 (TLR9), activate humoral and cellular immunity and are being developed as vaccine adjuvants to prevent or treat cancers, infectious diseases, and allergies. Free CpG ODNs have been used in many clinical trials implemented to verify their effects. However, recent research has reported that self-assembled CpG ODNs, protein/peptide–CpG ODN conjugates, and nanomaterial–CpG ODN complexes demonstrate higher adjuvant effects than free CpG ODNs, owing to their improved uptake efficiency into cells expressing TLR9. Moreover, protein/peptide–CpG ODN conjugates and nanomaterial–CpG ODN complexes are able to deliver CpG ODNs and antigens (or allergens) to the same types of cells, which enables a higher degree of prophylaxis or therapeutic effect. In this review, the author describes recent trends in the research and development of CpG ODN nanomedicines containing self-assembled CpG ODNs, protein/peptide–CpG ODN conjugates, and nanomaterial–CpG ODN complexes, focusing mainly on the results of preclinical and clinical studies. Keywords: CpG oligodeoxynucleotides, Toll-like receptor 9, immunostimulation, nanomedicine, adjuvant